2013
DOI: 10.1088/0031-9155/58/21/n287
|View full text |Cite
|
Sign up to set email alerts
|

Solar ultraviolet radiation response of EBT2 Gafchromic, radiochromic film

Abstract: Measurement of solar ultraviolet (UV) radiation is an important aspect of dosimetry for the improved knowledge of UV exposure and its associated health related issues. EBT2 Gafchromic film has been designed by its manufacturers as an improved tool for ionizing radiation dosimetry. The film is stated as exhibiting a significant reduction in UV response. However, results have shown that when exposed to UV from the 'bottom side' i.e. from the thick laminate side, the film exhibits a sensitivity to solar UV radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Accurate knowledge of the absorption spectrum of the radiochromic films and its behavior with dose helps to better understand their response to radiation . The optical absorption spectra of the EBT, EBT2, and EBT3 radiochromic films have been studied for their optical properties . In most of the existing literature, it has been shown that the irradiation of these films results in two principal absorption bands centered at 636 ± 3 and 585 ± 2 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate knowledge of the absorption spectrum of the radiochromic films and its behavior with dose helps to better understand their response to radiation . The optical absorption spectra of the EBT, EBT2, and EBT3 radiochromic films have been studied for their optical properties . In most of the existing literature, it has been shown that the irradiation of these films results in two principal absorption bands centered at 636 ± 3 and 585 ± 2 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Because the active layer of a Gafchromic film reacts to UV rays, 17 , 18 UV irradiation is effective only if appropriately applied. For instance, UV irradiation can markedly improve the uniformity of Gafchromic EBT (16) .…”
Section: Introductionmentioning
confidence: 99%
“…Application of radiochromic films for clinical X-ray dosimetry has, in essence, relied on dose-response curves (response in terms of film coloration) obtained through calibration. However, many intriguing properties of radiochromic films are not yet fully understood, including their responses to fluorescent light [3,4] and ultraviolet (UV) radiation [5][6][7][8]; the energy dependence of their responses [9][10][11][12][13]; the effects of polarization and scanning orientation [14][15][16]; and the effects of mechanical pressure [17] and auto-development [18], etc. In order to understand these intriguing properties, development of a theoretical model at both atomic and macroscopic scales is pertinent.…”
Section: Introductionmentioning
confidence: 99%